2019
DOI: 10.1155/2019/9602949
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of HTRA1 rs1120638, TIMP3 rs9621532, VEGFA rs833068, CFI rs10033900, ERCC6 rs3793784, and KCTD10 rs56209061 Gene Polymorphisms in Age-Related Macular Degeneration

Abstract: Background. To determine the impact of HTRA1 rs1120638, TIMP3 rs9621532, VEGFA rs833068, CFI rs10033900, ERCC6 rs3793784, and KCTD10 rs56209061 genotypes on the development of age-related macular degeneration (AMD) in the Lithuanian population. Methods. A total of 916 subjects were examined: 309 patients with early AMD, 301 patients with exudative AMD, and 306 healthy controls. The genotyping of HTRA1 rs11200638, TIMP3 rs9621532, VEGFA rs833068, CFI rs10033900, ERCC6 rs3793784, and KCTD10 rs56209061 was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 79 publications
0
8
0
5
Order By: Relevance
“…The rs5754227 [ 51 ], rs713685 [ 174 ], rs743751 [ 174 ], and rs5749482 [ 175 ] TIMP-3 intron variants have been particularly associated with an increased risk of AMD. Conversely, the rs9621532 TIMP-3 variant has been found to have a slight to moderate protective effect against AMD in some studies [ 47 , 49 , 165 , 176 ], as well as a protective effect against the development of MNV [ 177 ]—although other studies have found no association with AMD risk [ 178 , 179 ]. Finally, TIMP-3 variants rs6518799, rs756481, rs5749498, rs12170368, and rs1427385 have not been found to be associated with AMD [ 174 , 180 ].…”
Section: Extracellular Matrix (Ecm) Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs5754227 [ 51 ], rs713685 [ 174 ], rs743751 [ 174 ], and rs5749482 [ 175 ] TIMP-3 intron variants have been particularly associated with an increased risk of AMD. Conversely, the rs9621532 TIMP-3 variant has been found to have a slight to moderate protective effect against AMD in some studies [ 47 , 49 , 165 , 176 ], as well as a protective effect against the development of MNV [ 177 ]—although other studies have found no association with AMD risk [ 178 , 179 ]. Finally, TIMP-3 variants rs6518799, rs756481, rs5749498, rs12170368, and rs1427385 have not been found to be associated with AMD [ 174 , 180 ].…”
Section: Extracellular Matrix (Ecm) Remodelingmentioning
confidence: 99%
“…Patients with AMD have been found to have decreased retinal ERCC6 expression [ 286 ]. Mutations in the ERCC6 gene have been inconsistently associated with increased AMD risk [ 179 , 284 , 286 , 287 , 288 ] and may have a synergic effect with CFH mutations [ 284 ].…”
Section: Oxidative Stress Response and Photoreceptor Survivalmentioning
confidence: 99%
“…Vice versa, the clinical ophthalmologist may not be aware of the implications of a specific GWAS result for further recruitment needs. Often genetic studies deal exclusively with haplotype structures and allele frequencies but may not consider subtleties in phenotypic features [ 13 , 35 , 36 ]. Finally, clinical studies often bear the risk to leave out crucial knowledge of genetics in their interpretations and considerations [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the TIMP-3 rs9621532 polymorphism, which is also an intron variant, found contradictory results. Three of the reports found no statistical association between the polymorphism and the disease, while four reported that the C allele of TIMP-3 rs9621532 polymorphism was associated with a decreased risk of AMD [125,[194][195][196][197][198][199]. TIMP-3 rs9621532 polymorphism, being an intron variant, could be responsible for alteration in the gene expression.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors Of Metalloprmentioning
confidence: 95%